PENGARUH PERSONALISASI IKLAN ONLINE TERHADAP SIKAP DAN MINAT BELI KONSUMEN - Dini Agustina; Mukhamad Najib; Budi Suharjo (MIX: JURNAL ILMIAH MANAJEMEN, 2016)
Abstract. Personalized online advertisement is expected to minimize irritation of theadvertisements, and it may be beneficial to help consumers in searching informationbefore they are making a purchase decision. At present, consumers are having a diverseattitude toward the personalized online advertising, some are in favor, some are neutraland some are actually opposed to. Consumer's attitude play an important role consumerpurchase intention. Therefore, it is very critical for the personalized online advertisingto provide more value added to the consumer based on their purchase behavior bygiving the relevant information, while at the same time keeping the consumer's privacy.Despite of a lot of effort has been put in place to improve the effectiveness ofpersonalized online advertising, it has yet gained more positive response from theconsumer. This research is using the survey method that involving 200 respondents anddata analysis is using SEM (Structural Equation Modeling).